The interaction of Schumpeterian institutional entrepreneurship and Hayekian institutional change in innovative industries - Magnus Henrekson; Erik Lakomaa; Tino Sanandaji (Research Institute of Industrial Economics (IFN), 2021)
Innovation often takes place in entrepreneurial ecosystems. We use the history of the Silicon Valley venture capital model and the Hollywood motion picture industry to illustrate how specialized institutions that regulate these entrepreneurial ecosystems emerged through actions by business entrepreneurs, rather than being designed by policymakers. Schumpeterian entrepreneurs not only create new companies; they also create new institutions as an integral part of the restructuring process. At times, efforts of identifiable entrepreneurs are crucial, while in other instances institutional change results from a Hayekian process of emergence fueled by business entrepreneurs' efforts. Some institutions remain informal, whereas others become formalized. The greater room to forge institutions through business practices may in part account for the higher rates of entrepreneurship observed in common law countries.
Keywords: L26; M13; O31; P14; 330; Entrepreneurship policy; High-impact entrepreneurship; Innovation; Institutional entrepreneurship; Schumpeterian entrepreneurship